The impact of spectral resolution on satellite retrieval accuracy of CO2 and CH4 - Galli, André; Butz, André (Atmospheric measurement techniques, 2014)
Abstract. The Fourier-transform spectrometer on board the Japanese GOSAT (Greenhouse gases Observing SATellite) satellite offers an excellent opportunity to study the impact of instrument resolution on retrieval accuracy of CO2 and CH4. This is relevant to further improve retrieval accuracy and to optimize the cost-benefit ratio of future satellite missions for the remote sensing of greenhouse gases. To address this question, we degrade GOSAT measurements with a spectral resolution of ≈ 0.24 cm−1 step by step to a resolution of 1.5 cm−1. We examine the results by comparing relative differences at various resolutions, by referring the results to reference values from the Total Carbon Column Observing Network (TCCON), and by calculating and inverting synthetic spectra for which the true CO2 and CH4 columns are known. The main impacts of degrading the spectral resolution are reproduced for all approaches based on GOSAT measurements; pure forward model errors identified with simulated measurements are much smaller. For GOSAT spectra, the most notable effect on CO2 retrieval accuracy is the increase of the standard deviation of retrieval errors from 0.7 to 1.0% when the spectral resolution is reduced by a factor of six. The retrieval biases against atmospheric water abundance and air mass become stronger with decreasing resolution. The error scatter increase for CH4 columns is less pronounced. The selective degradation of single spectral windows demonstrates that the retrieval accuracy of CO2 and CH4 is dominated by the spectral range where the absorption lines of the target molecule are located. For both GOSAT and synthetic measurements, retrieval accuracy decreases with lower spectral resolution for a given signal-to-noise ratio, suggesting increasing interference errors.